Sentiments, financial markets, and macroeconomic fluctuations - Benhabib, Jess; Liu, Xuewen; Wang, Pengfei (Journal of Financial Economics, 2016)
This paper studies how financial information frictions can generate sentiment-driven fluctuations in asset prices and self-fulfilling business cycles. In our model economy, exuberant financial market sentiments of high output and high demand for capital increase the price of capital, which signals strong fundamentals of the economy to the real side and consequently leads to an actual boom in real output and employment. The model further derives implications for asymmetric nonlinear asset prices and for economic contagion and co-movement across countries. In the extension to the dynamic overlapping generations (OLG) setting, our model demonstrates that sentiment shocks can generate persistent output, employment, and business cycle fluctuations, and it offers some new implications for asset prices over business cycles.